Amelioration of salt‐induced damage on alfalfa by exogenous application of silicon. (30th August 2021) - Zhang, Weihong; Xie, Yan; Wu, Ya; Wassie, Misganaw; Li, Kai; Wang, Ziying; Li, Huiying; Liu, Dalin
Abstract: The present study was aimed to investigate the protective role of silicon (Si) from salt‐induced damages in alfalfa. Seedlings were treated with 200 mM NaCl plus three silicon levels (0, 0.75 and 1.5 mM) for 1 week. We observed that salt stress impacted plant growth remarkably, including height, root length, stem and leave weight, aboveground biomass and total biomass, chlorophyll a (chl a), chlorophyll b (chl b), total chlorophyll (total chl), chlorophyll fluorescence, K concentration and K/Na ratio. Consequently, electrolyte leakage (EL), superoxide dismutase (SOD) activity, Na concentration, proline, malondialdehyde (MDA), soluble sugar (SS) and soluble protein (SP) content were found to be raised significantly. After exogenously applying Si under salt stress, the EL, MDA, proline and Na content, except SOD activity, were observed to be dropped. Meanwhile, the chl a, chl b, and total chl and SS content, and chlorophyll fluorescence were found to be elevated. In terms of Si concentration, we found that the protective effects of Si were considerably better at lower concentration (0.75 mM) than higher (1.5 mM) one. Collectively, our results suggested that Si alleviate salt‐induced damage and promote alfalfa growth by changing physiological characteristics.